ChemInform Abstract: Synthesis and Structure Determination of CaSi1/3B2/3O8/3: A New Calcium Borosilicate. Issue 25 (3rd June 2013) - Veron, Emmanuel; et al., et al.
Abstract Crystalline CaSi1/3B2/3O8/3 is observed in situ by high‐temperature XRD during heating (first XRD reflections at 740 °C) from a corresponding glassy composition in the CaO—SiO2—B2O3 ternary system prepared by CaCO3, SiO2, and B2O3 mixtures (Pt crucible, 1200—1500 °C, 2 h, quenching).